Pengaruh Persepsi Tentang Pertimbangan Pasar Kerja dan Pengetahuan Akuntansi Terhadap Keinginan Mahasiswa Peminatan Audit Universitas Advent Indonesia (UNAI) untuk Berkarir di Bidang Akuntan Publik - Cheerfully Doanny Grace Hutagalung; Lorina Siregar Sudjiman (LP3M Universitas Putra Bangsa, 2022)
This study aims to determine the effect of student perceptions of labor market considerations and accounting knowledge on students' desire for a career in the field of Public Accountants. The method used is a causality study with a quantitative approach and uses primary data, namely distributing questionnaires to 76 students of Audit Specialization in 2022. The total population was sampled based on saturated sampling technique and the answers were processed using the SPSS 22 application. The results found were perceptions of labor market considerations having a constant value of 0.459, T count 4.896 > 1.992997 and Sig, 0.000 < 0.05, and accounting knowledge has a constant value of 0.365, T count 3.591 > 1.992997 and Sig, 0.001 < 0.05 indicating that the two variables partially have a positive and significant influence on the desire to have a career in the field of Public Accountants with a percentage of the coefficient of determination (R2) of 67.7%. And the F test produces F count 76.125 > 3.122103 and Sig. 0.000 < 0.05, proving that the two variables simultaneously have a positive and significant influence on the desire to have a career in the field of Public Accountants.